PS-005 Pharmaceutical interventions in an emergency department under a pharmaceutical care system. (24th February 2014) - Cabré Serres, M; García-Peláez, M; Payés Peich, M; Iglesias Lepine, ML; Gómez-Valent, M; Raich Montiu, L; De Castro Julve, M; Borràs Trias, L; Gorgas Torner, MQ
Abstract : Background: Clinical safety is an essential component of health care quality. The EVADUR study showed that 12% of patients who were in the emergency department (ED) had adverse events (AE). 70% of them were considered avoidable. Purpose: To describe pharmaceutical interventions (PI) conducted by a pharmaceutical care system (PCP) in an ED and calculate the impact of its continuous implementation. Materials and methods: We conducted a two-month descriptive study about PCP in ED. The system consisted of monitoring pharmacotherapy and detecting drug-related problems (DRP) of patients who had to be admitted and stay in the ED for 24 h. It also included checking stock medicines, monitoring restricted drugs, pharmacovigilance and drug information. 2 h a day was allocated for the PI. We excluded psychiatry, gynaecology and emergency paediatrics. We adapt and modify the classification of PI according to the Granada Third Consensus on PI indication, efficacy and safety. Results: During the study 1402 patients were admitted to the hospital from the ED, 351 (25%) of whom benefited from the PCP. We conducted 103 PI. The greater percentage of problems was omission of necessary medicines (23.3%), followed by adjustment of the medicines to the hospital guidelines (17.5%) and medicines that were not needed during the stay in the ED (9.7%). Classification of PI was similar between indication, efficacy and safety (37.9%, 31.1% and 31.1%, respectively). 79.6% of PI were accepted. Extrapolating data, if PCP had been applied to all patients admitted to hospital from the ED, it could have made ??412 PI. Conclusions: The presence of a pharmacist in the ED improves the detection, registration and resolution of DRP. A full-time pharmacist in the ED would optimise pharmacotherapy for all patients and resolve queries. Future studies are needed that allow us to determine the impact of this intervention when the patient is hospitalised. No conflict of interest.